Gorillas tender giants - Dash, Gary A.; Wedderun, Bridget ([S.l.] : Discovery Channel Video [production company] ; Petaling Jaya : Wawasan Videovan [distributor], 1999)
Early explores in central Africa brought back wild tales of gorillas as half-man, half-monster
Naskah 2 adalah bahan pembelian Kelab Pencinta Ilmu (KPI)
Executive producer, Tim Cowling ; editor, Anna Gregory
Narrator: Elliott Gould
Keywords: Gorillas